PENGARUH EARNINGS MANAGEMENT DAN GOOD CORPORATE GOVERNANCE TERHADAP EXPENSE STICKINESS - Hananto, Hari (Ultimaccounting Jurnal Ilmu Akuntansi, 2021)
Abstract”Expense stickiness is the thickness of the charge showed a response asymmetric load behavior towards a change in activity, ie when the activity decreases the burden will decline more slowly than when the activity increases. If a company's activity has decreased but also followed the rapid decline in the cost, also has been called Decrease expense stickiness, researchers predict there are motivation of management to manage earnings. The existence of good corporate governance, that with good corporate governance activities of companies that declined to follow a decreasing cost also for their efficiency on costs. It was concluded that good corporate governance also affects decreasing expense stickiness, although not as strong earnings management.The purpose of this study was to examine the pattern of expense stickiness whether companies in Indonesia tend to earnings management or good corporate governance to increase corporate profits. The population used in this study are all non-financial entities listed on the Indonesia Stock Exchange (BEI) in the period 2014-2015. To see the effect of earnings management to use variable expense stickiness total log administration and operational expense (SGA). As for the influence of good corporate governance to use variable expense stickiness total log administration and operational expense (SGA) or the FACT which is a variable of good corporate governance.The results of this study found that companies using earnings management do not lower the expense stickiness. This shows that company management directs the achievement of performance through real activities management rather than just accrual recognition of performance. As for good corporate governance tends to decrease the stickiness expense, prove that GCG is able to oversee management activities in managing the company. Asymmetric/ opportunistic management actions can be reduced through the effectiveness of the GCG mechanism. Keywords: Corporate Governance; Earnings Management; Expense Stickiness.